2021
DOI: 10.1186/s12870-021-03048-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought on photosynthesis, total antioxidant capacity, bioactive component accumulation, and the transcriptome of Atractylodes lancea

Abstract: Background Atractylodes lancea (Thunb.) DC, a medicinal herb belonging to the Asteraceae family, often faces severe drought stress during its growth. Until now, there has been no research on the effect of drought stress on the quality formation of A. lancea. Therefore, the present study aimed to study the effects of drought stress on A. lancea through physical and chemical analysis, and to reveal the related molecular mechanisms via transcriptome analysis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…For example, when subjected to drought stress, plants change their rate of respiration and photosynthesis. They slow down transpiration by controlling stomatal conductance, thus retaining moisture [ 1 , 2 , 3 ]. Salt stress is one of the most important abiotic stressors, which leads to ion imbalance and water loss through osmotic reactions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, when subjected to drought stress, plants change their rate of respiration and photosynthesis. They slow down transpiration by controlling stomatal conductance, thus retaining moisture [ 1 , 2 , 3 ]. Salt stress is one of the most important abiotic stressors, which leads to ion imbalance and water loss through osmotic reactions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results, Shi et al (2021) reported that photosynthetic parameters (P n , gs, C i , and T r ) and water potential were all decreased in Hordeum jubatum seedlings under drought stress. In addition, Zhang et al (2021) reported that drought stress caused declines in the chlorophyll content, P n and Gs values, and F v /F m ratio in Atractylodes lancea . However, it is worth noting that a lesser decline for these parameters (except T r ) was observed in tetraploids compared to the diploids, suggesting that tetraploid rootstock maintains higher photosynthetic activities after drought stress in our study ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The light energy is absorbed by LHCs and subsequently transferred to the photosynthesis reaction center (Huang et al, 2021). Photosynthesis is highly sensitive to water deficit, which is generally weakened under drought stress (Ma et al, 2016;Zhang et al, 2021). As known, stomata are highly sensitive to drought stress (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis is highly sensitive to water deficit, which is generally weakened under drought stress (Ma et al, 2016;Zhang et al, 2021). As known, stomata are highly sensitive to drought stress (Zhang et al, 2021). Given that stomata are channels for gas exchange in photosynthesis, closure or partial closure of stomata by drought stress largely reduced intercellular carbon dioxide (CO 2 ) concentration and sequenced inhibited photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation